5-메틸-1,2,4-옥사디아졸-3-일 화합물의 저용량 요법 및 제제 - KIELBASA WILLIAM BRIAN; MERGOTT DUSTIN JAMES (2023)
본 발명은 하기 화학식 I의 화합물: TIFFpct00030.tif3197, 또는 그의 제약상 허용되는 염을 제공하고, 여기서 화학식 I의 화합물, 또는 그의 제약상 허용되는 염은 0.1 mg/일 내지 5 mg/일의 화합물의 총 용량으로 경구 투여되는 것이고, 신경변성 타우병증, 예컨대 알츠하이머병, 전두측두엽 치매, 피질기저 증후군 및 진행성 핵상 마비를 포함한 신경변성 질환을 치료하는데 유용하다. The present invention provides a compound of Formula I:or a pharmaceutically acceptable salt thereof, wherein the compound of Formula I, or pharmaceutically acceptable salt thereof is administered orally with a total dose of the compound of 0.1 mg/day to 5 mg/day, useful for treating a neurodegenerative disease, including neurodegenerative tauopathies, such as Alzheimer's disease, frontotemporal dementia, corticobasilar syndrome, and progressive supranuclear palsy.